(untitled) (Journal of Global Arts Studies, 2025)
Background： With the transformation of social and educational needs, the deep integration of innovation and entrepreneurship education and professional education is increasingly important. Objective： Explore the integration mechanism of innovation and entrepreneurship education and professional education and its realization path, and finally build a set of theory system for the integration of the two. Methods: Based on the integration of innovation and professional education, this study proposes three key pathways: curriculum reform, faculty development and government university industry collaboration to address current challenges. Results: Curriculum design enables progressive training from theory to practice, faculty development fosters teaching innovation, and government-university-industry cooperation enhances practical and societal alignment, forming an integrated education framework. Conclusion: The integration of innovation and entrepreneurship education with professional education is a multi-actor, cross-system reform that shifts from knowledge-based to competency-based training, and from campus-centered to socially coordinated development, aiming to cultivate high-quality innovative talent.